The lost elements : the periodic table's shadow side - Fontani, Marco, 1969- (Oxford University Press, 2014)
The Periodic Table of Elements hasn''t always looked like it does now, a well-organized chart arranged by atomic number. In the mid-nineteenth century, chemists were of the belief that the elements should be sorted by atomic weight. However, the weights of many elements were calculated incorrectly, and over time it became clear that not only did the elements need rearranging, but that the periodic table contained many gaps and omissions: there were elements yet to be discovered, and the allure of finding one had scientists rushing to fill in the blanks. Supposed ""discoveries"" flooded laborat